Respiratory impedance and bronchodilator responsiveness in healthy children aged 2-13 years - Calogero, C.; Simpson, S.; Lombardi, E.; Parri, N.; Cuomo, B.; Palumbo, M.; De Martino, M.; Shackleton, C.; Verheggen, M.; Gavidia, T.; Franklin, P.; Kusel, M.; et al. (Wiley-Liss, Inc, 2013)
Background: The forced oscillation technique (FOT) can be used in children as young as 2 years of age and in those unable to perform routine spirometry. There is limited information on changes in FOT outcomes in healthy children beyond the preschool years and the level of bronchodilator responsiveness (BDR) in healthy children. We aimed to create reference ranges for respiratory impedance outcomes collated from multiple centers. Outcomes included respiratory system resistance (Rrs) and reactance (Xrs), resonant frequency (Fres), frequency dependence of Rrs (Fdep), and the area under the reactance curve (AX). We also aimed to define the physiological effects of bronchodilators in a large population of healthy children using the FOT. Methods: Respiratory impedance was measured in 760 healthy children, aged 2–13 years, from Australia and Italy. Stepwise linear regression identified anthropometric predictors of transformed Rrs and Xrs at 6, 8, and 10 Hz, Fres, Fdep, and AX. Bronchodilator response (BDR) was assessed in 508 children after 200 µg of inhaled salbutamol. Results: Regression analysis showed that Rrs, Xrs, and AX outcomes were dependent on height and sex. The BDR cut-offs by absolute change in Rrs8, Xrs8, and AX were −2.74 hPa s L−1, 1.93 hPa s L−1, and −33 hPa s L−1, respectively. These corresponded to relative and Z-score changes of −32%; −1.85 for Rrs8, 65%; 1.95 for Xrs8, and −82%; −2.04 for AX. Conclusions: We have established generalizable reference ranges for respiratory impedance and defined cut-offs for a positive bronchodilator response using the FOT in healthy children.